Role of liraglutide in brain repair promotion through Sirt1‐mediated mitochondrial improvement in stroke. Issue 3 (18th September 2019) - He, Weiliang; Wang, Haoyuan; Zhao, Congying; Tian, Xiaochao; Li, Litao; Wang, Hebo
Abstract: Brain repair, especially axonal sprouting, is critical to restore motor function in disabled stroke patients. Liraglutide (LG) is a new kind of long‐acting analogue of glucagon‐like peptide‐1 (GLP‐1) and has potential protective effects in stroke. The mitochondria participate in brain repair after cerebral injury. However, the mechanism of the effect of LG on brain repair and its potential influence on mitochondria in stroke remains obscure. Here, in focal cerebral cortical ischemic mice model, LG improved the motor functional recovery and promoted axonal sprouting by restoring the activities of isocitrate dehydrogenase, α‐ketoglutarate dehydrogenase, and succinate dehydrogenase. Moreover, LG remarkably increased the cell survival rate and revived the NeuN and GAP‐43 levels in cortical neurons under hydrogen peroxide (H2 O2 ) exposure. It was also observed that LG reduced the generation of reactive oxygen species, stabilized the mitochondrial membrane potential, enhanced the levels of adenosine triphosphate, enhanced activities of mitochondrial complex‐I, and decreased protein expression levels of fission‐1 in H2 O2 ‐injured cortical neurons. Additionally, LG suppressed the expressions of sirtuin 1 (Sirt1) in cortical neurons exposed to H2 O2 . Furthermore, knockdown of Sirt1 by short interfering RNA facilitated the LG‐mediated mitochondrial protection in cortical neurons under H2 O2 . Collectively, this data from the present study illustrated that LG exerted a promoting influence on brain repair, after cerebral ischemic injury, through Sirt1‐mediated mitochondrial improvement.